2006
DOI: 10.1212/01.wnl.0000219625.77625.aa
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based detection of white matter abnormalities in mild Alzheimer disease

Abstract: Voxel-wise comparison of whole-brain anisotropy revealed widely distributed disintegration of white matter in mild Alzheimer disease (AD). The white matter shows a different pattern of degeneration from gray matter and may be an independent factor in the progress of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
145
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 30 publications
27
145
3
1
Order By: Relevance
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, some studies reported changes in the anterior subregion (e.g. [20,21,46,82]), some in the posterior subregion [20,21,83,91], and some found no callosal changes [40,85,92]. This inconsistency in results may be the consequence of reduced sample size of studies considering discrete diagnostic categories of different clinical stages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings of studies on more homogeneous patients, such as those with mild AD, are discrepant. For example, Xie et al [82] found a decrease of FA in the genu and left anterior body of the CC, whereas Ulkmar et al [83] found a decrease of FA in the genu and splenium of the CC; other studies [84][85][86][87] found no differences in the CC in patients with mild AD.…”
Section: Diffusion-weighted Imaging and Diffusion Tensor Imaging Studiesmentioning
confidence: 98%
“…TBSS is a newer analytic technique developed to reduce the alignment and smoothing problems that have been reported with VBM (Smith et al, 2006(Smith et al, , 2007. Both approaches have been used to assess for differences in WM integrity in a variety of psychiatric disorders including MDD (Bae et al, 2006;Li et al, 2009;Xie et al, 2006).…”
Section: Introductionmentioning
confidence: 99%